Disiplin Kerja dan Pengaruhnya Terhadap Kinerja Karyawan pada PT Armada Samudra Global Jakarta - Eigis Yani Pramularso; Nurul Anggraeni (Yayasan Literasi Sains Indonesia, 2023)
In the company's operations, human resources have a very important role in achieving the planned targets in the vision and mission. One that supports increasing the role of human resources is applying work discipline to employees in carrying out all activities related to the work assignments that have been given. The purpose of this study was to determine the effect of work discipline on employee performance at PT Armada Samudra Global. Regarding the sample in this study, it was taken using a saturated sample technique by asking questions through questionnaires distributed to 40 employees. Data analysis in this study used correlation coefficients, determination coefficients, and simple regression. Previously, validity and reliability tests were also carried out using the SPSS 25 program data processing techniques. The results of this study illustrate that employee performance at PT Armada Samudra Global is positively and significantly influenced by work discipline. The coefficient of determination shows a large share of work discipline on employee performance. Other results related to the correlation coefficient show that there is a very strong relationship between work discipline and the performance of employees of PT Armada Samudra Global.